n + 4 chia hết cho n - 1
=> ( n - 1 ) + 5 chia hết cho n - 1
Mà n - 1 chia hết cho n - 1
=> 5 chia hết cho n - 1
=> n -1 thuộc Ư(5) = { 1 ; 5 }
=> n thuộc { 2 ; 6 }
Thì cứ giải từng con1 ùi lik-e cho
n2 + 2n - 3 chia hết cho n + 1
=> n2 + n + n - 3 chia hết cho n + 1
=> n ( n + 1 ) + n - 3 chia hết cho n + 1
Mà : n ( n + 1 ) chia hết cho n + 1
=> n - 3 chia hết cho n + 1
=> ( n + 1 ) - 4 chia hết cho n + 1
Mà : n + 1 chia hết cho n + 1
=> 4 chia hết cho n + 1
=> n + 1 thuộc Ư(4) = { 1 ; 2 ; 4 }
=> n thuộc { 0 ; 1 ; 3 }